(untitled) (Nigerian Journal of Technology, 2025)
Extreme rainfall events pose significant challenges to the design of flood control infrastructure, especially spillways. This study evaluates three scenarios for estimating the frequency factor, a vital component of the Hershfield method of determining probable maximum precipitation (PMP). The study examines the impact of multiple outliers on frequency factor estimation through three scenarios. The study employed the Hershfield procedure in the derivation. Daily annual maximum rainfall data was collected from three stations (Kano, Bauchi and Dutse). The data was subjected to outlier checks using the box and whisker plot for simplicity and easy visualization. The results were analyzed using the Analysis of Variance (ANOVA). The ANOVA results clearly showed the number of outliers and the selection of the highest observed daily rainfall depth () have a significant effect on the frequency factor. The frequency factor obtained ranges from 2.1 to 4.88. Among the three Scenarios, Scenario 2 provided a more reliable estimate due to its ability to account for extreme outliers effectively. The results underscore the importance of considering outliers in hydrologic analysis to avoid underestimating risks in flood-prone areas. This ensures that infrastructure is better equipped to withstand rare, high-magnitude rainfall events, reducing the risk of catastrophic failures.